A comprehensive characterization of volatile profiles of plum brandies using gas chromatography coupled to high resolution mass spectrometry. (15th September 2022) - Filatova, Maria; Bechynska, Kamila; Hajslova, Jana; Stupak, Michal
Abstract: Alike in case of other spirits, specific sensory properties of plum brandies, which are associated with aromatic compounds pattern, depend not only on a fruit quality but also on technology used for raw material processing. In this study, novel approach based on the non-target screening of (semi)volatile compounds by gas chromatography coupled to high-resolution mass spectrometry (GC–HRMS) was employed. The potential of this approach to distinguish plum brandies of different origin was investigated. To involve as many compounds as possible for assessment, three different sample handling strategies prior to instrumental analysis were tested: (i) no pre-treatment direct sample injection, (ii) liquid-liquid extraction by ethyl acetate, (iii) extraction of volatiles by head-space solid-phase microextraction (HS-SPME). The latter approach was selected for obtaining GC–HRMS volatiles fingerprints of a unique set of 41 plum brandy samples produced by the distilleries from Czech Republic and from Bulgaria. Multivariate statistical data analysis enabled construction of chemometric models for unbiased authentication of plum brandies, moreover, distinguishing between premium plum brandies and other ones from the Czech Republic was achieved. In addition, volatile compounds such as p -cymene, methyl eugenol and furfural were identified among the most significant 'markers' responsible for reliable classification of the samples. Highlights: Three sample preparation strategies were tested for isolation of plum brandies components. Non-target screening using SPME-GC-HRMS was applied to the analysis of unique set of plum brandies. Univariate statistics and chemometric methods were used for the processing of obtained data. Chemometric methods enable classification of plum brandy according to region of production and processing technology. Characteristic 'markers' were found and tentatively identified.